Kepemimpinan Dalam Pendidikan Islam (Pengertian, Karakteristik Kepemimpinan Rasulullah, Karakteristik Kepemimpinan Islam dan Keberhasilannya) - Alfi Alfarizhi Hidayat; Imamul Muttaqin (Lembag, 2024)
Leadership in Islamic education is a crucial element that influences the quality and effectiveness of the learning process. This research focuses on the definition of leadership from an Islamic perspective, identifying the characteristics of leadership exemplified by the Prophet Muhammad, as well as digging deeper into the common features of Islamic leadership that have proven successful in various educational contexts. Through a literature review and qualitative approach, this research seeks to clarify how leadership based on Islamic values can have a significant impact on the success of educational institutions. The Prophet Muhammad, as the ultimate example, demonstrated effective leadership through traits such as justice, trustworthiness, exemplary leadership, and good communication skills. These values not only build a strong leadership foundation, but are also relevant to be applied in modern education systems. In addition, the distinctive features of Islamic leadership, such as integrity, justice and responsibility, are important factors in the success of Islamic education. The results show that the application of Islamic leadership values can contribute to improving the overall quality of education, both in terms of character development and academic achievement. The study also provides practical recommendations for educational leaders in applying Islamic leadership principles and offers guidance for further research focusing on the practical application of Islamic leadership in contemporary education.